Answer:
![\sum ^{20} _{n \to \11} 4n](https://tex.z-dn.net/?f=%5Csum%20%5E%7B20%7D%20_%7Bn%20%5Cto%20%5C11%7D%204n)
Step-by-step explanation:
In order to write the series using the summation notation, first we need to find the nth term of the sequence formed. The sequence generated by the series is an arithmetic sequence as shown;
4, 8, 12, 16, 20...80
The nth term of an arithmetic sequence is expressed as Tn = a +(n-1)d
a is the first term = 4
d is the common difference = 21-8 = 8-4 = 4
n is the number of terms
On substituting, Tn = 4+(n-1)4
Tn = 4+4n-4
Tn = 4n
The nth term of the series is 4n.
Since the last term is 80, L = 4n
80 = 4n
n = 80/4
n = 20
This shows that the total number of terms in the sequence is 20
According to the series given 4 + 8 + 12 + 16 + 20+ . . . + 80
, we are to take the sum of the first 20terms of the sequence. Using summation notation;
4 + 8 + 12 + 16 + 20+ . . . + 80 = ![\sum ^{20} _{n \to \11} 4n](https://tex.z-dn.net/?f=%5Csum%20%5E%7B20%7D%20_%7Bn%20%5Cto%20%5C11%7D%204n)
Answer:
(1,4)
Step-by-step explanation:
Which ordered pair is a solution of the equation? y = 7 x − 3
a. (1,4) b. (-1,-4) c. both d. neither
Solution
y=7x-3
Solve by trying each ordered pair
a. (1,4)
x=1, y=4
Substituting the value of x and y into the equation
y=7x-3
4=7(1)-3
4=7-3
4=4
This is a true statement
b. (-1,-4)
x=-1, y=-4
Substitute the value into the equation
y=7x-3
-4=7(-1)-3
-4= -7-3
-4= -11
This is not a true statement
This true statement is when x=1 and y=4
So, the ordered pair (1, 4) is the solution
Answer:
![18\ pies](https://tex.z-dn.net/?f=18%5C%20pies)
Step-by-step explanation:
Let
x-------> the number of pies
we know that
-----> linear equation that represent the situation
solve for x
![5.75x-52.50=50](https://tex.z-dn.net/?f=5.75x-52.50%3D50)
![5.75x=50+52.50](https://tex.z-dn.net/?f=5.75x%3D50%2B52.50)
![5.75x=102.50](https://tex.z-dn.net/?f=5.75x%3D102.50)
![x=102.50/5.75=17.8](https://tex.z-dn.net/?f=x%3D102.50%2F5.75%3D17.8)
Round to the nearest whole number
![17.8=18\ pies](https://tex.z-dn.net/?f=17.8%3D18%5C%20pies)
Answer:
Step-by-step explanation:
let x = number of of hot dogs that 105 people will do
therefore
14 people = 21 hot dogs
105 people = x hot dogs
14 x 105 people = 21 x Xhotdogs
1470 = 21X
divide through by 21
1470/21 = 21X/21
70 = X
X = 70
therefore,
105 people will makev 70 hot dogs
Answer:
The Second one y=1/3x
Step-by-step explanation:
Because when you substitute x by 3 ( for example) then, you get y = 1
and that's right from the graph.